Exposure to movie smoking, antismoking ads and smoking intensity: an experimental study with a factorial design. Issue 3 (11th December 2009) - Harakeh, Zeena; Engels, Rutger C M E; Vohs, Kathleen; van Baaren, Rick B; Sargent, James
Abstract : Background: This study examines whether smoking portrayal in movies or antismoking advertisements affect smoking intensity among young adults. Methods: We conducted an experimental study in which 84 smokers were randomly assigned using a two (no-smoking versus smoking portrayal in the movie) by three (two prosocial ads, two antismoking ads or one of each) factorial design. Participants viewed a 60-minute movie with two commercial breaks and afterwards completed a questionnaire. Smoking during the session was allowed and observed. Results: Exposure to the movie with smoking had no effect on smoking intensity. Those who viewed two antismoking ads had significantly lower smoking intensity compared with those who viewed two prosocial ads. There was no interaction between movie smoking and antismoking ads. Baseline CO (carbon monoxide) level had the largest effect on smoking intensity. Conclusion: These findings provide further evidence to support antismoking ads placed with movies because of their possible effect on young adult smoking behaviour. However, caution is warranted, because nicotine dependence appears to be the primary predictor of smoking intensity among young adult smokers in this study.